Participación de la comunidad de Huanchaquito bajo en la gestión del patrimonio arqueológico de Gramalote como alternativa de promoción turística - Cruz Gonzalez, María del Carmen (2017)
ABSTRACT COMMUNITY INVOLVEMENT HUANCHAQUITO LOW IN ASSET MANAGEMENT AS AN ALTERNATIVE GRAMALOTE ARCHAEOLOGICAL TOURISM PROMOTION This research addressed the theme: "Participation of the Community of Huanchaquito Under the Archaeological Heritage Management Gramalote alternative tourism promotion" They tried to show, in the desire to involve the community, the management mechanisms archaeological heritage in the Site Gramalote, the same that is located in Sector Huanchaquito Low, District of Huanchaco, Trujillo Province. This heritage is very close to the community of the same name, also located adjacent to the local commune of the sector is therefore intended that involve, in order to participate actively in the tourist promotion of this heritage. The objectives was to establish alternatives to promote participation of the Community of Huanchaquito Under the Archaeological Heritage Management Gramalote alternative tourism promotion, in order to contribute to the identity and the cultural development of the community. With respect to the research methodology used, the ethnographic method that served to know the cultural characteristics of the community Huanchaquito Low, that is able to verify in situ the reality under study related to the independent variable of community identity was applied so as the deductive method - inductive that identified not only the theoretical indicators of the archaeological heritage of Gramalote stuff research. techniques were used as surveys and interviews, both residents of the community and their local authorities, the same that permit to demonstrate the validity of our hypothesis as the results obtained so far have indicated that the community Huanchaquito Low and managers of the commune have an idea of what is heritage and tourism, but in reality is not translated in their attitudes, so your regular lack of interest is translated in the low active participation for the proper functioning of tourism promotion of their cultural heritage.